2007
DOI: 10.1073/pnas.0701224104
|View full text |Cite
|
Sign up to set email alerts
|

Helical microtubule arrays in a collection of twisting tubulin mutants of Arabidopsis thaliana

Abstract: Anisotropic expansion of plant cells requires organized arrays of cortical microtubules. Mutations in microtubule-associated proteins and a particular mutation in ␣-tubulins were reported to cause abnormal microtubule arrays and result in helical growth in Arabidopsis thaliana. However, the way in which these mutations affect the organization of microtubules remains unknown. We here identified 32 Arabidopsis twisting mutants that have either missense or amino acid deletion mutations in ␣-or ␤-tubulins. Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(198 citation statements)
references
References 31 publications
5
192
1
Order By: Relevance
“…Similar phenotypes were reported for tortifolia and spiral mutants (Furutani et al, 2000;Buschmann et al, 2004;Shoji et al, 2004). Helical growth defects commonly correlate with an increased transverse alignment of MTs (Ishida et al, 2007), which are visible upon the overexpression of YFP-IQD11, GFP-IQD14, and GFP-IQD16 (Figs. 6I and 7C).…”
Section: Overexpression Of Iqd11 and Iqd14 Differentially Modulates Psupporting
confidence: 61%
See 2 more Smart Citations
“…Similar phenotypes were reported for tortifolia and spiral mutants (Furutani et al, 2000;Buschmann et al, 2004;Shoji et al, 2004). Helical growth defects commonly correlate with an increased transverse alignment of MTs (Ishida et al, 2007), which are visible upon the overexpression of YFP-IQD11, GFP-IQD14, and GFP-IQD16 (Figs. 6I and 7C).…”
Section: Overexpression Of Iqd11 and Iqd14 Differentially Modulates Psupporting
confidence: 61%
“…6, A-D), indicating the functionality of the fusion protein. Helical growth aberrations and altered leaf shape were reported for tomato sun lines (Wu et al, 2011) and often are associated with defects in MT functions (Buschmann et al, 2004;Ishida et al, 2007). Moreover, the growth defects are reminiscent of plants overexpressing LONGIFOLIA1/TON1 RECRUITING MOTIF2 (TRM2), which encodes a plant-specific MAP (Lee et al, 2006;Drevensek et al, 2012).…”
Section: Overexpression Of Iqd16 Alters Mt Organization and Cell Shapementioning
confidence: 99%
See 1 more Smart Citation
“…The simulations of Eren et al [2010] showed that changing the microtubule polymer dynamics as experimentally observed in Arabidopsis tua4 S178D and tua5 D251N twisted growth mutants [Ishida et al, 2007] was not sufficient to induce skewed arrays. Inspired by the conceptual framework for the role of CMT nucleation, and branch-form nucleation in particular, in CMT array orientation [Wasteneys and Ambrose, 2009], Eren et al [2010] used their 3D simulations with nonperiodic boundaries to test several scenarios with branch-form nucleation and boundary conditions such as increasing or decreasing the mean branch angle, introducing a bias for branching from one side of the mother CMT, and assigning only one of the end walls of the cylinder as a nonperiodic boundary.…”
Section: Factors That Results In Cmt Array Skewingmentioning
confidence: 88%
“…The tor2 mutant shows several distinct defects in the dynamics of cortical microtubules. Many of the observed aberrations argue for microtubules being hyperstabilized in the tor2 background, which is probably caused by a decreased GTP hydrolysis rate in tor2 microtubules (Ishida et al, 2007;Buschmann et al, 2009). Interestingly, the tor2 mutant shows right-handed cell expansion even in the single-celled leaf trichomes.…”
Section: Introductionmentioning
confidence: 99%